Getting to Know About NEET Phenomenon in Indonesia (Youth Who Are Not in Employment, Not in Education and Not in Training) - Sitompul, Thomson (International Journal of Economics, Business, and Entrepreneurship, 2024)
This research aims to determine the influence of population growth and employment rate on the economic growth in North Sumatera from 2004 to 2022. The type of data used in this research is secondary data obtained from the Central Provincial Statistics Agency of North Sumatra from 2004 to 2022 (time series data). The results of this research show that partially the population growth has a significant positive effect on the economic growth of North Sumatra from 2004 to 2022. Partially the employment rate has a significant positive effect on the economic growth of North Sumatra from 2004 to 2022. Simultaneously, population growth and employment rate have a significant effect on economic growth.